Pengaruh Digital Marketing Terhadap Keputusan Pembelian Produk Point Coffee Indomaret Melalui Instagram @pointcoffeeid - Salsabila, Meidiana (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
The digital age requires marketers to be able to understand the behavior of their consumers. Marketers must stay connected with consumers, such as increasing interaction and providing exclusive offers for their consumers. This is one of the challenges for business people, one of which is a culinary business with a coffee shop concept which is currently one of the favorite places for quite a lot of people, one of which is Point Coffee Indomaret. The utilization of technology must certainly be done by marketers today, namely social media, especially Instagram. Point Coffee Indomaret plunges into digital media as a form of marketing by having an Instagram account @pointcoffeeid. Seeing that Instagram is one of the most widely used social media. Therefore, researchers wrote this study to examine the effect of digital marketing on purchasing decisions for Point Coffee Indomaret products through Instagram @pointcoffeeid. This research is quantitative research with digital marketing as variable X and purchasing decisions as variable Y. This research was conducted using a survey method, namely distributing questionnaires to 100 respondents. Based on the results of calculations with SPSS 26, the regression test results show an R value of 0.679, meaning that there is a positive influence of the digital marketing variable (X) on the purchasing decision variable (Y). So that with an influence of 46.1%. In addition, the significance value is 0.000 which is less than 0.05 and, it is known that the tcount is 9.157> ttable 1.984. Thus, Ha is accepted and H0 is rejected, which means that the digital marketing variable (X) has an effect on the purchasing decision variable (Y) of Point Coffee Indomaret products via Instagram @pointcoffeeid.